Knowledge about preventive measures for the development of diabetic foot - Valdenia Maria de Sousa; Isadora Almeida de Sousa; Karine Rafaela de Moura; Lucas Sallatiel Alencar Lacerda; Maria da Glória Sobreira Ramos; Ana Roberta Vilarouca da Silva (Universidade Federal do Ceará, 2020)
Objective: to analyze the knowledge of people with diabetes mellitus about preventive measures for the development of diabetic foot. Methods: cross-sectional study, carried out with 171 diabetic people treated in the Family Health Strategy. A form was applied to obtain sociodemographic and clinical variables and a scale to assess the level of knowledge. For analysis, descriptive and inferential statistics were used. Results: 65.5% had little knowledge. The question with the highest rate of correct answers was the non-use of a hot water bag on the feet (92.3%), however, the question with the highest rate of errors was: use open shoes at home and to go out, (66.8 %). The score of the instrument's total score was influenced by gender (p≤0.001). Conclusion: the participants had a low level of knowledge about preventive measures and were unaware of important self-care habits, such as using appropriate footwear and not hydrating between the toes.